Wind Energy in Brazil and Preliminary Assessment of Wind Resources in Tangara da Serra, Mato Grosso State - Ferreira, Jhonatan; Oliveira, Tarsila (Latin American Journal of Energy Research, 2026)
The growing global demand for energy, driven by economic expansion, has intensified the search for sustainable alternatives to fossil fuels. Among renewable energy sources, wind power has gained increasing relevance worldwide. In Brazil, installed wind energy capacity reached 33.3 GW in February 2025, distributed across 1,109 wind farms and accounting for 15.9% of the national electricity matrix, with an estimated potential ranging from 300 to 500 GW. This paper presents a literature review of wind energy production in Brazil and provides a preliminary assessment of the technical feasibility of installing wind turbines in the municipality of Tangará da Serra, Mato Grosso State. The analysis draws on anemometric data from the Brazilian National Institute of Meteorology (INMET) and published studies. Results indicate that the mean annual wind speed in the region (~6 m/s at 50 m height) falls below the conventional threshold for economically viable wind generation (7–8 m/s), although low-wind-speed turbine technologies may improve this outlook.
Keywords: Wind energy